Pengaruh Kepercayaan, Persepsi Harga, Lokasi dan Word of Mouth Terhadap Keputusan Pembelian Perumahan Taman Gaharu Kabupaten Kendal - Bangkit Kartika Siwi; Ali Maskur (Universitas Batanghari, 2022)
This study aims to analyze the effect of trust, price perception, location and word of mouth on purchasing decisions. The object under study is PT Taman Gaharu Bersinar Semarang city and the independent variables in the study are trust, price perception, location and word of mouth and the dependent variable is purchasing decisions. The population in this study are consumers who buy property products from PT Teman Gaharu Bersinar property in Semarang City with a minimum age of 17 years by taking a sample of 100 respondents. The sampling technique in this study used purposive sampling, which is a sampling technique with certain criteria. The data used in this study are primary data, using a questionnaire as a research instrument. The analytical tools used are validity test, reliability test, F test, coefficient of determination (R²) test, multiple linear regression and t assisted by SPSS version 16. The results show that trust has no significant negative effect on purchasing decisions, price perception has no positive effect. significant effect on purchasing decisions, location and word of mouth have a significant positive effect on purchasing decisions.